النظام المائي للمياه الجوفية الحرة بين حوضي نهري الغمقة والأبرش - جنوب طرطوس (Latakia University Journal -Basic Sciences Series, 2016)
Natural changes in the level of ground water through time is gaining great importance in evaluating the water system and to provide a lot of information about groundwater movement , which allows the assessment of the water situation public water layer in the study area .We adopted our measurements in groundwater levels frequencies on a private network monitoring hydrogeological She is the author of 26 wells distributed over the entire area of the region studied were carried out in some measurements for a period of six years. The study found that groundwater system of climate type (water division line) is directly linked to seep from rainfall and seepage from canals and irrigation water plays a significant role in the pose, which is characterized by Baltkareh and periodic quarterly in the annual changes of the levels, and the stability and balance in the conditions of these elevations, and the general direction of movement of groundwater will be from the east and north-east towards the west and southwest and Askew Hydraulic 0.005 a faddish topographic situation and the general trend of the cracks and fissures in the area.التغيرات الطبيعية لمنسوب المياه الجوفية خلال الزمن تكتسب أهمية كبرى في تقويم النظام المائي وتقديم الكثير من المعلومات حول حركة المياه الجوفية، الأمر الذي يسمح بتقويم الوضع المائي العام للطبقة المائية في منطقة الدراسة.اعتمدنا في قياساتنا ترددات مناسيب المياه الجوفية على شبكة رصد هيدروجيولوجية خاصة وهي مؤلفة من 26 بئراً موزعة على كامل مساحة المنطقة المدروسة نفذت في بعضها قياسات لمدة ست سنوات . وقد تبين من الدراسة أن نظام المياه الجوفية من النوع المناخي(خط التقسيم المائي) يرتبط ارتباطاً مباشراً بالرشح من الهطولات المطرية كما يلعب الرشح من قنوات ومياه الري دورا لا بأس به في تشكله، وهو يتصف بالتكرارية والدورية الفصلية في التغيرات السنوية للمناسيب، وبالاستقرار والتوازن في أوضاع هذه المناسيب، والاتجاه العام لحركة المياه الجوفية يكون من الشرق والشمال الشرقي باتجاه الغرب والجنوب الغربي وبميل هيدروليكي 0.005وهو يساير الوضع الطبوغرافي والاتجاه العام السائد للصدوع والتشققات في المنطقة.